Quantifying Preferences in Drug Benefit‐Risk Decisions. Issue 5 (24th April 2019) - Tervonen, Tommi; Angelis, Aris; Hockley, Kimberley; Pignatti, Francesco; Phillips, Lawrence D.
Abstract : Benefit‐risk assessment is used in various phases along the drug lifecycle, such as marketing authorization and surveillance, health technology assessment (HTA), and clinical decisions, to understand whether, and for which patients, a drug has a favorable or more valuable profile with reference to one or more comparators. Such assessments are inherently preference‐based as several clinical and nonclinical outcomes of varying importance might act as evaluation criteria, and decision makers must establish acceptable trade‐offs between these outcomes. Different healthcare stakeholder perspectives, such as those from patients and healthcare professionals, are key for informing benefit‐risk trade‐offs. However, the degree to which such preferences inform the decision is often unclear as formal preference‐based evaluation frameworks are generally not used for regulatory decisions, and, if used, rarely communicated in HTA decisions. We argue that for better decisions, as well as for reasons of transparency, preferences in benefit‐risk decisions should more often be quantified and communicated explicitly.